PML Surfs into HIPPO Tumor Suppressor Pathway - Strano, Sabrina; Fausti, Francesca; Di Agostino, Silvia; Sudol, Marius; Blandino, Giovanni (Frontiers in Oncology, 2013)
Growth arrest, inhibition of cell proliferation, apoptosis, senescence and differentiation are the most characterized effects of a given tumor suppressor response. It is becoming increasingly clear that tumor suppression results from the integrated and synergistic activities of different pathways. This implies that tumor suppression includes linear, as well as lateral, crosstalk signaling. The latter may happen through the concomitant involvement of common nodal proteins. Here, we discuss the role of Promyelocytic leukemia protein (PML) in functional cross-talks with the HIPPO and the p53 family tumor suppressor pathways. PML, in addition to its own anti-tumor activity, contributes to the assembly of an integrated and superior network that may be necessary for the maximization of the tumor suppressor response to diverse oncogenic insults.